1990
DOI: 10.1182/blood.v76.1.221.bloodjournal761221
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-thalassemia caused by a large (62 kb) deletion upstream of the human alpha globin gene cluster

Abstract: We describe a family in which alpha-thalassemia occurs in association with a deletion of 62 kilobases from a region upstream of the alpha globin genes. DNA sequence analysis has shown that the transcription units of both alpha genes downstream of this deletion are normal. Nevertheless, they fail to direct alpha globin synthesis in an interspecific hybrid containing the abnormal (alpha alpha)RA chromosome. It seems probable that previously unidentified positive regulatory sequences analogous to those detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
3
12
0
3
Order By: Relevance
“…Human a globin mRNA expression was evaluated in each of four hybrids carrying a different, mutated copy of chromosome 16. As previously reported (Hatton et al, 1990), a basal level of expression was seen in a hybrid containing the (aa)RA chromosome (Figure 6b) but in the others, human a globin mRNA, if present, was below the level of detection by the RNase protection assay. We found no evidence for aberrant expression of the 4 globin gene which remains intact on the (aa)IJ chromosome (data not shown).…”
Section: Gene Expression In the Absence Of Hs -40supporting
confidence: 83%
See 3 more Smart Citations
“…Human a globin mRNA expression was evaluated in each of four hybrids carrying a different, mutated copy of chromosome 16. As previously reported (Hatton et al, 1990), a basal level of expression was seen in a hybrid containing the (aa)RA chromosome (Figure 6b) but in the others, human a globin mRNA, if present, was below the level of detection by the RNase protection assay. We found no evidence for aberrant expression of the 4 globin gene which remains intact on the (aa)IJ chromosome (data not shown).…”
Section: Gene Expression In the Absence Of Hs -40supporting
confidence: 83%
“…Hybrids representing the abnormal chromosomes studied here were designated as follows (aa)RA, H-101 (Hatton et al, 1990); (aa)CMO, CMOSN (Flint et al, 1994); (aa)TAT, TATA (Wilkie et al, 1990); --MC, LCSN (Vickers and Higgs, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5). We have now demonstrated that the (aa)RA chromosome accounts for the a thalassaemia phenotype in this family [30].…”
Section: A Thalassaemia Associated With a Large (62 Kb) Deletion Upstmentioning
confidence: 58%